Performance of waste concern organic fertilizer on the growth and yield of T. aman rice in two AEZs of Bangladesh - Islam, MR; Saha, PK; Zaman, SK; Uddin, MJ (Dhaka University Journal of Biological Sciences, 2019)
Two field experiments were conducted in two AEZs of Bangladesh viz. AEZ 28 and AEZ 3 to test the performance of waste concern organic fertilizer (WCOF) on the growth and yield of T. aman rice. The test sites were selected in the BRRI farm, Gazipur under AEZ 28 and BRRI farm Rangpur under AEZ 3. The experiments were done by using six treatments where T1 = Absolute control, T2 = NPKS @ 80-35-40-10 kg/ha, T3 = T2 + 1 t WCOF/ha, T4 = 75% of T2 + 1 t WCOF/ha, T5 = 50% of T2 + 2 t WCOF/ha and T6 = 2 t WCOF/ha. The application of WCOF in combination with chemical fertilizer significantly increased plant height, panicle number, grain and straw yields of T. aman rice over control in both AEZs. It was observed that the application of WCOF @ 1 t/ha + 75% of T2 (NPKS @ 80-35-40-10 kg/ha) produced higher yields. The study revealed that the treatments T4 and T5 may be the most economically viable fertilizer management packages for T. aman rice cultivation in AEZ 28 while the treatment T4 may be recommended for AEZ 3. Dhaka Univ. J. Biol. Sci. 28(2): 177-185, 2019 (July)